Validation of primary production model of the desert shrub Larrea tridentata using soil-moisture augmentation experiments - J. F. Reynolds; Gary L. Cunningham (Oecologia, 1981)
In previous papers we have described and verified a primary production model of the desert shrub Larrea tridentata. Here we address the validation phase of the evaluation of this model. Two versions of the model which differ in the priority scheme used for allocating carbon to reproductive or vegetative organs were compared on the basis of their usefulness and reliability over a range of soil-moisture conditions. Over an entire growing season when soil-moisture conditions were near "normal" both versions of the model were adequate predictors of total above-ground vegetative growth and one was an adequate predictor of reproductive growth as well. A more detailed analysis revealed that the versions varied in the range of soil-moisture conditions over which they were adequate and that neither was adequate when soil-moisture had remained high for extended periods. The validation process has revealed some likely areas for model improvement to increase adequacy.
//NMSU//US-IBP//
Keywords: article; articles; journal; journals; Larrea,productivity model; Larrea,soil-moisture augmentation; model, Larrea; model,primary production; plant, Larrea; rainfall simulation,Larrea